Human Development Report 2009 - United Nations Development Programme (United Nations, 2009)
For many people around the world moving away from their home town or village can be the best – sometimes the only – option open to improve their life chances. The report explores how better policies towards mobility can enhance human development. It traces the contours of human movement – who moves where, when and why, and argues for practical measures that can improve prospects on arrival, which in turn will have large benefits both for destination communities and for places of origin. The report fixes human development firmly on the agenda of policy makers who seek the best outcomes from increasingly complex patterns of human movement worldwide.